Metabolic Dysfunction-Associated Steatotic Liver Disease Is Linked to Environmental Sustainability: The Role of the Mediterranean Diet - García, Silvia; Bouzas, Cristina; Ródenas-Munar, Marina; Cepeda, Violeta; Ugarriza, Lucía; Casares, Miguel; Gómez, Cristina; Mateos, David; Tur, Josep A. (Nutrients, 2025)
Background: Metabolic dysfunction-associated steatotic liver disease (MASLD) and climate change are major global health challenges. Aim: Our aim was to assess the relationship between intrahepatic fat content (IFC) and diet-related environmental impact in a Mediterranean diet (MD)-based intervention. Design: The design included a six-month longitudinal analysis within the frame of a FLIPAN randomized controlled trial, including 60 participants aged 40–60 years with MASLD, metabolic syndrome and obesity. Methods: IFC expressed as a percentage (%IFC) was measured by magnetic resonance imaging, and dietary intake was assessed via a validated food frequency questionnaire (FFQ). Environmental impacts of diets were estimated using life cycle assessment data from the Agribalyse® database, focusing on greenhouse gas (GHG) emissions, water use, energy use and land use. A composite sustainability score was also calculated. Changes in liver fat and environmental footprints were analyzed using a general linear model (GLM) adjusted for within-subject variability and partial correlation analysis adjusted for energy intake, MD adherence and body weight. Results: The participants with the highest %IFC reduction group in the GLM showed the highest decreases in GHG emissions and land use. Water use increased in this same group. Energy use and the composite sustainability score did not differ significantly between groups. Higher %IFC reductions were also associated with higher MD adherence and lower visceral fat. When the adjusted partial correlation analysis for the environmental parameters was performed, only water use remained significant. Conclusions: Higher reductions in %IFC were linked to dietary patterns with lower GHG emissions and land use and higher water use. However, when adjusted by energy intake, MD adherence and body weight in continuous modeling, only higher water use was related to lower %IFC. These findings highlight the complexity of achieving environmentally sustainable and health-promoting diets.